THE INFLUENCE OF SOCIAL MEDIA STRATEGIES ON ONLINE SHOPPING BEHAVIOUR AMONG UNIVERSITY STUDENTS: A STATISTICAL ANALYSIS - Nur Syazazlin Mohd Sauli; Siti Hasma Hajar Mat Zin; Mohd Hanafi Azman Ong (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This research investigates the influence of various social media strategies on the online purchasing habits of university students. Using descriptive statistics, independent t-tests, ANOVAs, and chi-square tests, the study identifies significant trends and differences in consumer behaviour when shopping online. A total of 382 students from Universiti Teknologi MARA (UiTM), Seremban Campus, participated in the study. Primary data were collected through an online questionnaire. The findings reveal that respondents generally display a positive attitude toward online shopping, with a moderate to high level of agreement. No statistically significant differences were found between male and female respondents regarding online shopping behaviours. However, a significant difference was observed across the three faculties involved in the study. Additionally, a statistically significant correlation was found between social media usage and gender, indicating that female students tend to spend more time on social networks, particularly within the 3–5 hour and over 5 hour daily usage categories. The study validates the substantial influence of social media on consumer purchasing decisions in the digital age. These insights are valuable for marketers seeking to optimise their digital marketing strategies. Future research should explore the long-term impact of different types of social media content on consumer loyalty and brand perception across various demographic segments.